A night on call or an overnight shift does not reduce residents’ empathy: a randomized crossover multicenter survey - Michiko Mizobe; Hitomi Kataoka; Hiroshi Yamagami; Chikao Ito; Yasuaki Koyama; Erika Yawata; Takashi Shiga (BMC Medical Education, 2019)
Abstract Background Studies have shown that sleep deprivation may reduce empathy among medical students. Yet, little is known about the empathy after a night on call or an overnight shift among resident physicians. Hence, we aimed to examine whether a night on call or an overnight shift reduces the physicians’ empathy. Methods We conducted a multicenter randomized crossover survey using the Jefferson Scale of Physician Empathy (JSE). A total of 260 physicians who worked at academic hospitals and community hospitals in Japan in 2016 were recruited and randomized into two groups. Group A first completed the JSE prior to a night on call or an overnight shift; then, 8 weeks later, Group A completed the JSE after a night on call or an overnight shift. Group B first completed the JSE after a night on call or an overnight shift; then, 8 weeks later, Group B completed the JSE prior to a night on call or an overnight shift. Statistical analyses were performed to compare the JSE scores of pre- and post-night on call or overnight shifts. Results A total of 117 Group A physicians and 112 Group B physicians returned a completed JSE. The overall response rate was 88.08%. There was no significant difference in the JSE scores between pre- and post-night on call or overnight shift. (Group A before night vs Group B after night, p = 0.40, Group A after night vs Group B before night, p = 0.68). Conclusion As per our results, a night on call or an overnight shift did not reduce the Japanese physicians’ empathy. To the best of our knowledge, this is the first study on physicians’ empathy after a night on call or an overnight shift.